Generation of transgene-free canker-resistant Citrus sinensis cv. Hamlin in the T0 generation through Cas12a/CBE co-editing - Jia, Hongge; Omar, Ahmad A.; Xu, Jin; Dalmendray, Javier; Wang, Yuanchun; Feng, Yu; Wang, Wenting; Hu, Zhuyuan; Grosser, Jude W.; Wang, Nian (Frontiers in Plant Science, 2024)
Citrus canker disease affects citrus production. This disease is caused by Xanthomonas citri subsp. citri (Xcc). Previous studies confirmed that during Xcc infection, PthA4, a transcriptional activator like effector (TALE), is translocated from the pathogen to host plant cells. PthA4 binds to the effector binding elements (EBEs) in the promoter region of canker susceptibility gene LOB1 (EBEPthA4-LOBP) to activate its expression and subsequently cause canker symptoms. Previously, the Cas12a/CBE co-editing method was employed to disrupt EBEPthA4-LOBP of pummelo, which is highly homozygous. However, most commercial citrus cultivars are heterozygous hybrids and more difficult to generate homozygous/biallelic mutants. Here, we employed Cas12a/CBE co-editing method to edit EBEPthA4-LOBP of Hamlin (Citrus sinensis), a commercial heterozygous hybrid citrus cultivar grown worldwide. Binary vector GFP-p1380N-ttLbCas12a:LOBP1-mPBE:ALS2:ALS1 was constructed and shown to be functional via Xcc-facilitated agroinfiltration in Hamlin leaves. This construct allows the selection of transgene-free regenerants via GFP, edits ALS to generate chlorsulfuron-resistant regenerants as a selection marker for genome editing resulting from transient expression of the T-DNA via nCas9-mPBE:ALS2:ALS1, and edits gene(s) of interest (i.e., EBEPthA4-LOBP in this study) through ttLbCas12a, thus creating transgene-free citrus. Totally, 77 plantlets were produced. Among them, 8 plantlets were transgenic plants (#HamGFP1 - #HamGFP8), 4 plantlets were transgene-free (#HamNoGFP1 - #HamNoGFP4), and the rest were wild type. Among 4 transgene-free plantlets, three lines (#HamNoGFP1, #HamNoGFP2 and #HamNoGFP3) contained biallelic mutations in EBEpthA4, and one line (#HamNoGFP4) had homozygous mutations in EBEpthA4. We achieved 5.2% transgene-free homozygous/biallelic mutation efficiency for EBEPthA4–LOBP in C. sinensis cv. Hamlin, compared to 1.9% mutation efficiency for pummelo in a previous study. Importantly, the four transgene-free plantlets and 3 transgenic plantlets that survived were resistant against citrus canker. Taken together, Cas12a/CBE co-editing method has been successfully used to generate transgene-free canker‐resistant C. sinensis cv. Hamlin in the T0 generation via biallelic/homozygous editing of EBEpthA4 of the canker susceptibility gene LOB1.